Professional Practice and Ethical Issues Related to Physical Restraint and Seclusion in Schools. (September 2016) - Scheuermann, Brenda; Peterson, Reece; Ryan, Joseph B.; Billingsley, Glenna
Use of physical restraint and seclusion procedures in schools continues to be controversial, and foster proposals for federal and state legislation and regulation. Despite much discussion about what policies are needed, there has been little discussion about the professional practice issues and the ethical issues related to these practices. The purpose of this report is to present six clusters of professional practice and ethical issues that have not heretofore been specifically identified. To do so, we will examine the codes of professional practice and ethics of organizations representing educators who work with students with severe behavioral challenges. To illustrate these issues, we use real-world case examples from media stories and official reports about problems resulting from restraint and seclusion. Although individuals may disagree regarding decisions about these ethical issues, these questions should be a part of any policy discussion related to professional practice regarding these issues, and they have rarely been addressed in the restraint and seclusion policy debate. In addition, they are also questions that must be examined by all professional educators for them to assure adherence to the professional practice and ethical codes for their field.